Reserve fund assessment amount prediction method and device - XU XIANG (2020)
The invention provides a reserve fund assessment amount prediction method and device. The method comprises the steps of obtaining historical balance information under a deposit subject; and then according to the historical balance information and the average balance information under each deposit subject in a set period, determining a reserve fund assessment amount in a preparation period, and further predicting the reserve fund assessment amount, thereby greatly saving manpower and material resources. 本发明提供的一种准备金考核金额预测方法及装置，通过获取存款科目下的历史余额信息；然后根据所述历史余额信息以及设定周期内每个存款科目下的平均余额信息确定准备期内的准备金考核金额，进而能够对准备金考核金额进行预测，大大节约人力物力。